PERBANDINGAN PENGARUH LATIHAN ROCKET JUMP DAN INCREMENTAL VERTICAL HOP TERHADAP DAYA LEDAK OTOT TUNGKAI PADA TIM BOLAVOLI PUTRI SVC PEKANBARU - Evariani, Ineke; ', Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: From the observation of researchers in the field in the women’s volleyball team SVC Pekanbaru. Weakness in the players in the exercise as well as in volleyball competition, that was infirmnity explosive power in the leg was bloking. There was apparent when performing blocking often did not fit of hands.There was also at the time of blocking the opponent simply smashed the ball into the field and missed a team SVC. The purpose of this research was the researchers wanted to know the effect of excercise rocket jump and incremental vertical hop on leg muscle explosive power volleyball SVC Pekanbaru. The population in this study was 12 peoples. Instrument in this study was vertical jump. Test data collection techniques with normality test α=0,05 thitung 4,32 > ttabel 2,015, homogeniteity test α=0,05 thitung 2,02 > ttabel 2,015 , hypothesis test α=0,05 thitung 6,98 > ttabel 1,812. It can be concluded tha there are significant excercise of rocket jump and incremental vertical and incremental vertical hop against the leg muscle explosive power in women’s volleyball SVC Pekanbaru.Keywords: explosive power, rocket jump, incrementala vertical hop